Integration of Production Scheduling & Transportation/Distribution Scheduling in A Supply Chain - Rawat, Saurav (2017)
In recent years, supply chain management (SCM) has become a common norm for most of the manufacturing or even service industries and in order to strive in the market, they need to make continuous efforts to improve it. Two very important aspects of supply chain are production and transportation and their scheduling. It is necessary to schedule them optimally, in order to achieve maximum performance and profits. Traditionally, both of these process were scheduled and sequentially optimized separately due to their complexity. But in recent years, integration of Supply Chain Management, Production scheduling and Transportation Scheduling (Delivery of goods) has been studied and practised together, to further improve the supply chain performance and overall costs. This report deals with the study of different integration methods and techniques, which has been developed and practised by the researchers and practitioners, throughout the years. This report explains various terms regarding integration and scheduling, additionally gives an brief overview about the different algorithms, which has been used in this field of study. A time frame (Chronological Order) method has been used and most of the studies in this area, are ordered according to their published year, so that the reader can get an idea, about the progression of production scheduling and transportation scheduling integrations research and implementation. Following, the report compares the literature provided and discusses about the gaps and problems, present in them. Afterwards, it ends with some suggestions and possible future directions for this field of study. Keywords: Supply Chain Integration; Production Scheduling; Transportation Scheduling; Integration; Operation Research; Delivery Integration; Supply Chain Integration; Heuristics; NP- Hard.